HUBUNGAN ANTARA PENDAMPINGAN BELAJAR ORANG TUA DENGAN HASIL BELAJAR TEMATIK MUATAN PENDIDIKAN KEWARGANEGARAAN KELAS V SD SE-GUGUS 7 PONJONG GUNUNGKIDUL - Indah Indah; Nadziroh Nadziroh (Universitas Sarjanawiyata Tamansiswa, 2019)
The purpose of this study was to determine a positive and significant relationship between parental learning assistance with thematic learning outcomes content of Citizenship Education for 5th-grade Elementary Schools Cluster 7 Ponjong Gunungkidul. This type of research is quantitative. The population of this research is the 5th-grade students of Ponjong Gunungkidul Elementary School Cluster 7 consisting of 4 schools and the total number of students is 84. Determination of the sample in this study using the determination of the number of samples from a particular population of Isaac and Michael for an error of 5% then obtained the number of samples is 69 students. The data collection technique used a questionnaire to determine the level of learning assistance from parents and documentation to find out student PTS learning outcomes. The results showed that there was a significant and positive relationship between parental learning assistance and the learning outcomes of 5th-grade students of the Ponjong Gunungkidul Cluster 7 Elementary School.